Mechanical regulation of stem-cell differentiation by the stretch-activated Piezo channel - He, Li; Si, Guangwei; Huang, Jiuhong; Samuel, Aravinthan D. T.; Perrimon, Norbert (Nature (London), 2018)
Stem cells of the Drosophila midgut sense mechanical signals in vivo through the stretch-activated ion channel Piezo, which is expressed on previously unidentified enteroendocrine precursor cells. Stretch-activated ion channel drives cell differentiation The effect of mechanical cues on the behaviour of cells in culture is well documented, but such effects are more difficult to study in vivo . Norbert Perrimon and colleagues find that stem cells of the Drosophila gut sense mechanical signals in vivo through the stretch-activated ion channel Piezo. Piezo is expressed in a subset of enteroendocrine precursor cells. Loss of Piezo reduces the differentiation of the enteroendocrine lineage in adults, while the over expression of this gene in gut stem cells has the reverse effect. Further analysis shows that Piezo activates the calcium signalling pathway in response to mechanical stimuli. Somatic stem cells constantly adjust their self-renewal and lineage commitment by integrating various environmental cues to maintain tissue homeostasis. Although numerous chemical and biological signals have been identified that regulate stem-cell behaviour, whether stem cells can directly sense mechanical signals in vivo remains unclear 1 . Here we show that mechanical stress regulates stem-cell differentiation in the adult Drosophila midgut through the stretch-activated ion channel Piezo. We find that Piezo is specifically expressed in previously unidentified enteroendocrine precursor cells, which have reduced proliferation ability and are destined to become enteroendocrine cells. Loss of Piezo activity reduces the generation of enteroendocrine cells in the adult midgut. In addition, ectopic expression of Piezo in all stem cells triggers both cell proliferation and enteroendocrine cell differentiation. Both the Piezo mutant and overexpression phenotypes can be rescued by manipulation of cytosolic Ca 2+ levels, and increases in cytosolic Ca 2+ resemble the Piezo overexpression phenotype, suggesting that Piezo functions through Ca 2+ signalling. Further studies suggest that Ca 2+ signalling promotes stem-cell proliferation and differentiation through separate pathways. Finally, Piezo is required for both mechanical activation of stem cells in a gut expansion assay and the increase of cytosolic Ca 2+ in response to direct mechanical stimulus in a gut compression assay. Thus, our study demonstrates the existence of a specific group of stem cells in the fly midgut that can directly sense mechanical signals through Piezo.